The Land Targeting Tools testing report - Nanjala, Catherine Topister; Notenbaert, An (2025)
The Land Targeting Tools is a web application that is made of three tools: Land Suitability, Land Similarity and Land Statistics. This report documents the functioning of the new version of the three modules, the user friendliness of the tools and provides recommendations and improvements that could be done to enhance the usability of the tools.